2015
DOI: 10.1002/bit.25578
|View full text |Cite
|
Sign up to set email alerts
|

Robust kinetics of an RNA virus: Transcription rates are set by genome levels

Abstract: In order to persist in nature, RNA viruses have evolved strategies to grow in diverse host environments. To better understand how such strategies might work, we used qRT-PCR to measure viral RNA species during cellular infections by a model RNA virus, vesicular stomatitis virus (VSV). Absolute levels of the VSV major transcript and genome were measured for infections in BHK and PC3 cells, across different multiplicities of infection (MOI 1, 10, 100), in the absence or presence of protein synthesis, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Diverse viruses might evoke different dynamics of IFN expression. The k 1, related to viral replication, and k 2 , related to viral ability to initiate anti-viral signal are closely related to virus type [ 37 40 ]. Our analysis revealed that the increase in value of k 1 or k 2 resulted in earlier onset of the IFNβ M and IFNλ1 M ( Fig 2D and 2E ) as well as greater values of SD ( Fig 2F and 2G ), indicating that diverse virus types significantly affected variability in IFN induction among multiple cells.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse viruses might evoke different dynamics of IFN expression. The k 1, related to viral replication, and k 2 , related to viral ability to initiate anti-viral signal are closely related to virus type [ 37 40 ]. Our analysis revealed that the increase in value of k 1 or k 2 resulted in earlier onset of the IFNβ M and IFNλ1 M ( Fig 2D and 2E ) as well as greater values of SD ( Fig 2F and 2G ), indicating that diverse virus types significantly affected variability in IFN induction among multiple cells.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, multiple infection with identical viral genomes can also alter infection outcomes. Such cooperation was documented for VSV and HIV, where rates of transcription and replication were enhanced with increasing multiplicity of infection (MOI) 23, 24 . Similarly, faster kinetics of virus production were seen at high MOI for poliovirus and IAV 19, 25 .…”
Section: Introductionmentioning
confidence: 92%
“…Processes that affect the latent time include primary transcription, which entails using the viral RNA polymerase associated with the entering viral genome to make viral mRNA, synthesis of viral proteins, replication of viral genomes, secondary transcription, and further viral protein synthesis. Recent measures and kinetic modeling of VSV early infection suggest that cellular resources for primary transcription and protein synthesis are not limiting (42), making these initial steps unlikely targets for interference by defective genomes. However, during secondary transcription and translation, as essential components for genome replication are synthesized, diversion of these resources to DIP genome replication, rather than viral genomic replication, reduces available levels of genomic template for production of viral mRNA and subsequent synthesis of viral proteins (6,7,37,73).…”
Section: Chosen Modelmentioning
confidence: 99%
“…Vesicular stomatitis virus (VSV), grown on diverse cell cultures, has served for more than 50 years as a model for the study of DIPs (5,39). Moreover, quantitative mathematical and computational models have been developed to describe the kinetics of VSV replication in cells (40)(41)(42), its intracellular interaction with DIPs (43,44), and its population dynamics (29).…”
mentioning
confidence: 99%